2017
DOI: 10.1002/sctm.16-0363
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Derived Extracellular Vesicles as Mediators of Anti-Inflammatory Effects: Endorsement of Macrophage Polarization

Abstract: Mesenchymal Stem Cells (MSCs) are effective therapeutic agents enhancing the repair of injured tissues mostly through their paracrine activity. Increasing evidences show that besides the secretion of soluble molecules, the release of extracellular vesicles (EVs) represents an alternative mechanism adopted by MSCs. Since macrophages are essential contributors toward the resolution of inflammation, which has emerged as a finely orchestrated process, the aim of the present study was to carry out a detailed charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
359
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 447 publications
(410 citation statements)
references
References 50 publications
25
359
0
2
Order By: Relevance
“…However, Lipo‐NPs caused substantial reduction in inflammatory cytokines, including interleukin 1 alpha (IL1α), IL‐6, and TNF‐α, which was further enhanced by GBZ loading (Figure 7D). Similar reductions in inflammatory cytokines have previously been noted in response to ADSC EVs, particularly with TNF‐α33 and IL‐6 67. Lipo‐NPs alone did not reduce the levels of GM‐CSF, but Lipo‐NPs loaded with GBZ did (Figure 7D).…”
Section: Resultssupporting
confidence: 79%
“…However, Lipo‐NPs caused substantial reduction in inflammatory cytokines, including interleukin 1 alpha (IL1α), IL‐6, and TNF‐α, which was further enhanced by GBZ loading (Figure 7D). Similar reductions in inflammatory cytokines have previously been noted in response to ADSC EVs, particularly with TNF‐α33 and IL‐6 67. Lipo‐NPs alone did not reduce the levels of GM‐CSF, but Lipo‐NPs loaded with GBZ did (Figure 7D).…”
Section: Resultssupporting
confidence: 79%
“…Activated mesenchymal stem cells can exhibit immunomodulatory properties [55][56][57]. In this context, IFN- synergizes with TNF- and/or IL-1 for activating mesenchymal stem cells which become immunosuppressive and then can inhibit T cell proliferation [56].…”
Section: Mesenchymal Stem Cells Control Osteosarcoma Development: Potmentioning
confidence: 99%
“…MSC-derived EVs may contain a diverse cargo, including proteins, mRNAs, microRNAs (miRNAs), and mitochondria, the functional effects of which remain largely unknown (9,(23)(24)(25). MSC-derived EVs alone are capable of recapitulating many of the beneficial effects of MSC whole-cell therapy (25)(26)(27)(28). Phinney and colleagues observed the transfer of MSC mitochondria and miRNAs via EVs to human macrophages in a model of silicosis and found that mitochondria enhanced macrophage bioenergetics, whereas miRNAs suppressed Toll-like receptor signaling (24).…”
mentioning
confidence: 99%